2013
DOI: 10.1109/jphot.2013.2276758
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Quantum Barrier Thickness in the Multiple-Quantum-Well Active Region of GaInN/GaN Light-Emitting Diodes

Abstract: The dependence of the polarization-induced electric field in GaInN/GaN multiplequantum-well light-emitting diodes (LEDs) on the GaN quantum barrier (QB) thickness is investigated. Electrostatic arguments and simulations predict that a thin QB thickness reduces the electric field in the quantum wells (QWs) and also improves the LED efficiency. We experimentally demonstrate that the QW electric field decreases with decreasing QB thickness. The lower electric field results in a better overlap of electron and hole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…As the result, the electric field in the QW is increased, and the electric field in the barrier is decreased. 37,38 Therefore, thicker barrier of the c-plane and ð10 13Þ SQW produces more titling in QW and less tilting in the barrier. It is also shown that the tilting is stronger in the c-plane SQW than in the semipolar ð10 13Þ SQW because of stronger polarization.…”
Section: Barrier Thicknessmentioning
confidence: 99%
“…As the result, the electric field in the QW is increased, and the electric field in the barrier is decreased. 37,38 Therefore, thicker barrier of the c-plane and ð10 13Þ SQW produces more titling in QW and less tilting in the barrier. It is also shown that the tilting is stronger in the c-plane SQW than in the semipolar ð10 13Þ SQW because of stronger polarization.…”
Section: Barrier Thicknessmentioning
confidence: 99%
“…7,8 Therefore, the total thickness of GaInN/GaN MQWs cannot be increased, and the maximum thickness is dozens of nanometers. 9,10 It is well-known that the piezoelectric field is intrinsically absent on nonpolar m-plane substrates. 6 If the m-plane can be adopted in the GaInN/GaN active layer, internal quantum efficiency drop can be effectively suppressed.…”
Section: Introductionmentioning
confidence: 99%
“…Light-emitting diodes (LEDs) and laser diodes are widely used in our daily life, including in illumination, backlights of smartphones, and large displays. Among III–V group semiconductor materials, GaN-based LEDs have contributed significantly to energy saving in recent years because of their long life and high luminous efficiency. Specifically, GaN/GaInN multiple quantum well (MQW) LEDs grown on polar c -plane structures have been widely developed and commercialized. , However, an internal electric field (piezoelectric field) commonly exists in the MQW active layer grown on c -plane substrates because of piezoelectric polarization. , The quantum confinement Stark effect (QCSE), because of the piezoelectric field, decreases the radiative recombination probability and the internal quantum efficiency. , Therefore, the total thickness of GaInN/GaN MQWs cannot be increased, and the maximum thickness is dozens of nanometers. , It is well-known that the piezoelectric field is intrinsically absent on nonpolar m -plane substrates . If the m- plane can be adopted in the GaInN/GaN active layer, internal quantum efficiency drop can be effectively suppressed. , Additionally, the thickness of the QW can be increased without clear degradation of crystalline quality .…”
Section: Introductionmentioning
confidence: 99%
“…The favorable periods and thickness of InGaN/GaN QWs for high brightness and high EQE under high injection current (above several tens of mA) of blue LEDs are reported [1618]. In the reports, nine periods of InGaN/GaN QWs grown on patterned sapphire substrates (PSSs) show a significant improvement of light emission power and droop properties of EQE [16].…”
Section: Introductionmentioning
confidence: 99%
“…The best optical and electrical performances of blue LEDs are demonstrated if the active region consists of 12 periods of InGaN/GaN QWs at the injection current 42 A/cm 2 [17]. Apparent reduction of EQE droop and enhancement of IQE are demonstrated for the thickness of QB reduced from 24.5 to 9.1 nm in the simulation results of InGaN/GaN LEDs [18]. Si doping in proper thickness and numbers of QBs in InGaN/GaN QWs is crucial for further promotion of brightness and efficiency of InGaN blue LEDs operating at high injection current.…”
Section: Introductionmentioning
confidence: 99%